2009
DOI: 10.1002/eji.200839091
|View full text |Cite
|
Sign up to set email alerts
|

Peptide mimics of two pneumococcal capsular polysaccharide serotypes (6B and 9V) protect mice from a lethal challenge with Streptococcus pneumoniae

Abstract: Anti-polysaccharide immunity is a key facet of protection against several bacterial pathogens. Problems exist with current polysaccharide vaccines and alternative strategies that deliver a protective response are needed. We have identified immunological peptide mimics of type 6B and 9V pneumococcal capsular polysaccharides that could be used as vaccine antigens. Peptides mimicking antigenic properties of serotype 6B capsular polysaccharide were obtained from a phage-displayed peptide library expressing dodecam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…pneumoniae strain D39 (NCTC 7466) was chosen because it is a well-characterized strain. We have previously shown it to be virulent in in vivo (12) and ex vivo studies with ciliated epithelia (13,14). The D39 pneumolysin-deficient mutant (ΔPLY) and wild-type strains were propagated in tryptic soy broth medium as described previously (15).…”
Section: Virus and Bacterial Growth Conditionsmentioning
confidence: 99%
“…pneumoniae strain D39 (NCTC 7466) was chosen because it is a well-characterized strain. We have previously shown it to be virulent in in vivo (12) and ex vivo studies with ciliated epithelia (13,14). The D39 pneumolysin-deficient mutant (ΔPLY) and wild-type strains were propagated in tryptic soy broth medium as described previously (15).…”
Section: Virus and Bacterial Growth Conditionsmentioning
confidence: 99%
“…The most important feature lies in developing vaccines and efforts to obtain effective therapies for pathogens, such as Plasmodium vivax (Demangel et al 1998), Sc. mansoni (Arnon et al 2000), Cryptococcus neoformans (Fleuridor et al 2001), P. falciparum (Casey et al 2004;Sabo et al 2007), Fasciola hepatica (Villa-Mancera et al 2008, 2011, Streptococcus pneumonia (Smith et al 2009), Toxoplasma gondii (Cunha-Júnior et al 2010), and Helicobacter pylori (Li et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Phage display libraries were used to identify peptide mimics of the polysaccharide capsule of serotypes 6B and 9V. 45 These mimics protected mice from lethal challenge with S pneumoniae. A monoclonal antibody, Dob1, has also been identified that binds polysaccharide from serotypes 6A, 6B, 6C, and 19A and is capable of opsonizing S pneumoniae from these serotypes.…”
Section: Progress In the Identification Of Vaccine Candidatesmentioning
confidence: 99%